Surgical repair for transverse facial cleft: two flaps with a superiorly rotated single Z-plasty lateral to the commissure. Issue 4 (4th July 2019) - Zhou, Pan; Qiu, Lin; Liu, Yan; Li, Tianwu; Ding, Xionghui
Abstract: Various techniques have been performed for repairing transverse facial clefts. This study aimed to investigate an optimal method for repairing transverse facial clefts. Twenty-seven patients from 2008 to 2017 were evaluated. Their mean age at repair was 6.7 months with a follow-up period of 6 months to 10 years. A method using an inferior lip-based triangular mucosa flap and a superior lip-based rectangular vermilion-mucosa flap was designed for transposition. The orbicularis oris was reconstructed by using everting mattress suture. The skin was sutured using linear cutaneous closure with a single superiorly rotated Z-plasty lateral to the commissure. A postoperative symmetrical commissure was obtained owing to complete contraction with the new commissure directed 2 or 3 mm medial to the symmetrical point on the lips individually for the 27 patients. Lateral displacement of the reconstructed commissure was not observed. The patients showed a plump and symmetrical cheek on the cleft side. Twenty-one patients with hemifacial microsomia achieved a prominent improvement compared with their preoperative appearance, although the postoperative cheeks still did not show fullness because of the lesser facial tissue on the cleft side. In the early follow-up period, most patients showed a minimal scar during movement. However, the scar became thinner and symmetrical oral movement was achieved over time. This method obtained a natural oral movement without a conspicuous scar and was reliable and remarkable for the postoperative appearance of commissural symmetry. We conclude that this is an optimal method to repair transverse facial clefts.